Mulching influence on the reestablishement of ground-dwelling arthropod communities after a wildfire - Puga, João Ricardo Lavoura (2016)
In the past decades Portugal has been one of the Mediterranean countries most affected by wildfires. In order to find better fire mitigation strategies for ecosystem recovery and land management a crescent number of studies all over the world have been conducted. The use of mulch is currently used to protect soils from erosion after a fire. However, the effects of mulching in communities such as ground-dwelling arthropods have been neglected. Hence, this study aimed to contribute to a better understanding of the long-term effects of chopped eucalypt bark mulch on the recovery of ground-dwelling arthropod communities five years after the wildfire and the respective mulching application. This study was conducted in a burnt Eucalyptus plantation located in north-central of Portugal, which was mulched immediately after the fire. The results of this study showed that five years after the wildfire and the mulching application the ground-dwelling arthropod communities are similar between mulched and untreated sites and among positions along the slope. In general, no significant relations were found between environmental variables and the ground-dwelling arthropod community. A high homogeneity of ground cover classes and ground-dwelling arthropod communities’ composition was obtained for both treatments. The most abundant orders were Hymenoptera and Collembola, associated with omnivore and microbial feeders that seem to be beneficiated by the high availability of litter. Coleoptera and Araneae had the higher richness of morphospecies, being mostly compodes by ground predatory families. Analysis of ecological function suggests that the high availability of litter could be an important and selective factor for the current ground-dwelling arthropod community in the study area. Globally it seems that the effects of mulching on the recovery of ground-dwelling arthropod communities in Eucalyptus plantations are diluted in a long-term after fire. However these findings do not discard potential short-term effects of mulching on particular groups of arthropods during the early period after its application on the burnt area, which are still ignored.